God the suffering Father and Israel the abandoned child : Hosea 11 and Psalm 80 in intertextual conversation - Treurnicht, Schalk (Stellenbosch : Stellenbosch University, 2019)
Thesis (MTh)--Stellenbosch University, 2019.